2015
DOI: 10.1039/c5tc01611h
|View full text |Cite
|
Sign up to set email alerts
|

Fast direct synthesis and compaction of phase pure thermoelectric ZnSb

Abstract: ZnSb is a promising low cost, non-toxic thermoelectric material, but large scale applications require development of fast and easy synthesis methods. Here a thorough investigation of the influence of synthesis parameters (pressure, sintering time, maximum temperature, stoichiometry) are explored in direct one step Spark Plasma Sintering synthesis of ZnSb pellets from Zn and Sb powders. The homogeneity of the produced pellets is studied using conventional powder X-ray diffraction (PXRD), synchrotron PXRD, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 50 publications
3
24
0
Order By: Relevance
“…64,65 However, our facile, low-temperature solution-phase synthesis could be useful as a means of mitigating this problem, as it allows for reduction in grain size or nanostructuring. 13,[66][67][68][69] Characterization of LiZnSb using solid state NMR. Surface passivating ligands are a critical feature of phases prepared by low-temperature solution-phase synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…64,65 However, our facile, low-temperature solution-phase synthesis could be useful as a means of mitigating this problem, as it allows for reduction in grain size or nanostructuring. 13,[66][67][68][69] Characterization of LiZnSb using solid state NMR. Surface passivating ligands are a critical feature of phases prepared by low-temperature solution-phase synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Xiong et al have reported that the volume fraction of Sb phase was estimated to be ∼2wt.% by Rietveld refinement in a hotpressed sample [19] at 673K in vacuum followed by an evacuated quartz ampoule and annealed at 673K for 80h. A recent study on SPS-samples showed also that Sb phase domains were distributed along the samples, accompanied with Zn 4 Sb 3 on the surface [92]. Another difference is the final grain size of pellets.…”
Section: Thermoelectrics For Power Generation -A Look At Trends In Thmentioning
confidence: 99%
“…Considering that one of the favourable aspects of ZnSb from a commercial point of view is the low materials cost, there have been several efforts where the cost efficiency of the synthesis technique is important [92][93][94].…”
Section: Thermoelectrics For Power Generation -A Look At Trends In Thmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the thermoelectric properties of bulk ZnSb are suitable for improvement by nanostructuring. 24,25 Several reports on densely packed pellets of ZnSb have appeared recently, utilizing techniques like ball-milling, [26][27][28][29][30] spark plasma sintering, 31 and cryogenic milling. 32 Optimization of doping levels and alloying elements have significantly enhanced the thermoelectric properties of ZnSb, 22,27,33,34 0021-8979/2016/119(12)/125103/10/$30.00…”
Section: Introductionmentioning
confidence: 99%